Varanusia nom. nov., a replacement name for Lizardia Nogueira, Hutchings & Carrerette, 2015 (Annelida: Terebellidae), preoccupied by Lizardia Pleijel & Rouse, 2005 - Nogueira, João Miguel De Matos; Hutchings, Pat; Carrerette, Orlemir (Zootaxa, 2015)
Nogueira et al. (2015) proposed the generic name Lizardia to accommodate L. quasimodo Nogueira, Hutchings & Carrerette, 2015, an abranchiate terebellid from Lizard Island with only 9 pairs of notopodia beginning from segment 4 and bearing both distally smooth and distally serrated notochaetae, and neuropodia beginning from segment 6.